2013
DOI: 10.1038/nature12209
|View full text |Cite
|
Sign up to set email alerts
|

Rev-Erbs repress macrophage gene expression by inhibiting enhancer-directed transcription

Abstract: Rev-Erbα and Rev-Erbβ are nuclear receptors that regulate the expression of genes involved in the control of circadian rhythm1,2, metabolism3,4, and inflammatory responses5. Rev-Erbs function as transcriptional repressors by recruiting NCoR/HDAC3 co-repressor complexes to Rev-Erb response elements in enhancers and promoters of target genes6-8, but the molecular basis for cell-specific programs of repression is not known. Here, we present evidence that in macrophages, Rev-Erbs regulate target gene expression by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
531
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(557 citation statements)
references
References 30 publications
24
531
2
Order By: Relevance
“…This is consistent with previous findings that Rev-erb␣ is not transcriptionally active at all of its cistromic binding sites in the liver (44,48). The Rev-erb␣ dependence of eRNA transcription in WAT but not in other tissues may not only reflect the activity of the Klb enhancers but could also be playing a direct role in transcriptional regulation, as reported in macrophages (57).…”
Section: Discussionsupporting
confidence: 81%
“…This is consistent with previous findings that Rev-erb␣ is not transcriptionally active at all of its cistromic binding sites in the liver (44,48). The Rev-erb␣ dependence of eRNA transcription in WAT but not in other tissues may not only reflect the activity of the Klb enhancers but could also be playing a direct role in transcriptional regulation, as reported in macrophages (57).…”
Section: Discussionsupporting
confidence: 81%
“…S3F). Collectively, our data show the mechanism by which KLK3e forms a functional complex with AR and Med1 to promote transcription, supporting the findings that transfer of full enhancer activity to a target promoter depends on enhancer-bound transcription factors and enhancerderived RNA transcripts (14).…”
Section: Significancesupporting
confidence: 66%
“…The activity of eRNAs was shown to augment the expression of not only neighboring but also intrachromosomally distant genes to convey enhancer-dependent transcription (12,13). Recently, the 5′-GRO-seq data have revealed that sequencespecific transcription factors and eRNA transcripts are required for transfer of full enhancer activity to a target promoter (14). Moreover, eRNAs have been shown to configure a chromatin state that facilitate transcription factors binding on the target promoters at defined genomic loci (15).…”
Section: Klk3e/ar/med1 Complex | Chromosomal Loopingmentioning
confidence: 99%
“…Some enhancer-like RNAs were reported to interact with mediators and change the chromatin conformation to activate the target genes (60). eRNAs have been reported to establish the chromatin looping and generate the interaction of the enhancers with their target genes (61)(62)(63). In the current study, the lncPrep+96kb knockdown did not change the histone acetylation pattern in the Hepa1-6 cell (Fig.…”
Section: Discussionmentioning
confidence: 53%